Transport emission modelling based on a bottom-up approach to facilitate sustainable transport planning - Anna Charly; Brian Caulfield (Sustainable Futures)
Modelling road transport emissions is critical in designing sustainable policies. Traditional emission models follow a top-down approach by distributing the emissions for a region based on the vehicle stock. This research envisions a bottom-up approach based on the link traffic volume, fleet, and emission factors to develop an improved model for link-based transport emissions. The proposed model is integrated with the National Transport Model for Ireland and considers CO2, NOX and PM2.5 emissions from all vehicles and fuel types, including electric vehicles (EVs). Further, the impact of increasing EV trip share outside the major urban regions is evaluated. Analysis showed that emissions generated by a single vehicle were much higher in rural areas than urban ones. Results indicate that replacing a conventional car with an EV in rural counties could reduce up to 3.4 kg of CO2 during a morning peak hour instead of 2.2 kg in urban areas.